Penerapan Perawatan Kaki Terhadap Resiko Ulkus Pada Penderita Diabetes Mellitus di Wilayah Kelurahan Sukarami - Feliciyanvi Uverni; Sanny Frisca; Novita Elisabeth Daeli (Jurnal Ventilator, 2024)
Diabetes mellitus is a degenerative disease characterized by high blood sugar levels caused by impaired insulin secretion in the body. The main chronic complications in diabetes mellitus sufferers are macrovascular, microvascular and neuropathy. One of the consequences of peripheral neuropathy is ulcers. To prevent trauma to the feet or ulcers, you can provide foot care. This research aims to develop the application of foot care that contains the risk of ulcers in diabetes mellitus sufferers in Sukarami Village. This research uses qualitative research with a case study approach. There were 3 respondents who suffered from diabetes mellitus with inclusion and exclusion criteria. This research was carried out by providing foot care interventions carried out for 4 consecutive days in diabetes mellitus sufferers. The results of implementing EBP showed that there was an improvement in the condition of the respondents' feet. It is hoped that the results of this research will increase independent foot care behavior to prevent the risk of ulcers.